Associação entre duração do sono e consumo de alimentos ultraprocessados em adolescentes de uma capital do Brasil: um estudo longitudinal - Barreto, Erika Mayra de Almeida (2023)
Objective: To longitudinally analyze the relationship between sleep duration and consumption of ultra-processed foods in adolescent students. Methods: Longitudinal study, carried out between 2014 and 2017, with adolescents aged 10 to 14 years old in the base year. Data collection was carried out through face-to-face interviews, individually. The selected variables were sociodemographic factors, sleep duration, sedentary behavior, weight, height, BMI/age, food consumption, level of physical activity. Sleep duration was considered the independent variable, which was divided into quartiles, using the 75th quartile as a reference, and the percentage of consumption of ultra-processed foods (in relation to the total calories consumed by the individual) was considered the dependent variable. Results: When analyzing the four established models of generalized estimation equations and dividing sleep time by quartiles, we highlight the results found in the 4th quartile as it concentrates adolescents with the longest sleep time. In model 1, we have the relationship between sleep time and percentage of energy of ultra-processed foods, adolescents who are in the fourth quartile of sleep have a reduction of 1.4% (95% CI - 2.49; - 0.28, standard error 0.57) of the energy percentage from ultra-processed foods. Model 2 showed a decrease of 1.6% (95% CI -2.66; -0.48, standard error 0.56) in the energy percentage of consumption of ultra-processed foods. In model 3, a decrease in the percentage of energy from ultra-processed foods of 1.5% (95% CI -2.66; -0.48, standard error 0.56). In model 4, reduction in the intake of 1.4% (CI 95% -2.72; -0.10, standard error 0.67) of the energy percentage of foods classified as ultra-processed. Conclusion: Sleep influenced the consumption of ultra-processed foods in adolescents, showing that as sleep time increases, consumption of foods classified as ultra-processed decreases.